Handbook of Clinical Child Neuropsychology - Reynolds, Cecil R. (Springer, 2017)
The past decade has brought important advances in our understanding of the brain, particularly its influence on the behavior, emotions, and personality of children and adolescents. In the tradition of its predecessors, the third edition of the Handbook of Clinical Child Neuropsychology enhances this understanding by emphasizing current best practice, up-to-date science, and emerging theoretical trends for a comprehensive review of the field. Along with the Handbook’s impressive coverage of normal development, pathology, and professional issues, brand-new chapters highlight critical topics in assessment, diagnostic, and treatment